EFEKTIFITAS PENGGUNAAN LAPORAN KEUANGAN SEDERHANA BAGI PEDAGANG KAKI LIMA PASAR TRADISIONAL KOTA PARIAMAN - Nichy Oktaviani; Patria Nagara; Fathiah Fathiah (Ensiklopedia of Journal, 2022)
One of the causes of the lack knowledge of street vendors is the low level financial literacy. On the other hand, financial literacy is one of the key principles of entrepreneurship that will assist in making decisions and carrying out activities that have financial consequences. When the financial literacy of street vendors  is low, this will be a barrier in achieving business success considering that street vendors operate in a dynamic and complex environment. Most of the problems faced by business actors are related to financial statements that are not clear and do not even have financial statements. Therefore, we must prepare maximum accounting concepts for street vendors so that they are easy to understand and can be applied to managed businesses. Financial reports in traditional markets are dominated by traders who have quite large businesses. So in this study, the researchers tried to provide an effective use of simple books (simple financial statements) for street vendors in traditional markets in order to determine the net profit earned in one period. The method used in this research is descriptive quantitative. The study used a Pre-Experimental design, namely One-Group Pretest-Posttest Design. This research only involved 1 experimental group without a control group. This design compares the situation before and after being treated with the use of simple books (simple financial statements) to see net income. Data collection techniques used are questionnaires, interviews, and documentation studies. While the data analysis technique used will be descriptive statistical analysis which refers to the existing interval values to measure effectiveness and describe the results of these measurements. From the results of data analysis calculated based on each indicator, it is obtained; First, it can be understood to obtain 3.168. Second, Relevance got 3,196. Third, Reliability got 3,172. Fourth, comparability obtained 3.172. From some of these indicators, the average variable is 3,177 which is in the interval value of 2.45 - 3.2 and shows effectiveness. So, the conclusion of this study is that the use of Simple Financial Statements for Street Vendors in Pariaman Traditional Markets has been effective.Keywords: Effectiveness, Financial Report